2017
DOI: 10.1002/cncr.31087
|View full text |Cite
|
Sign up to set email alerts
|

Individualized outcome prognostication for patients with laryngeal cancer

Abstract: Suboptimal reliability and accuracy limit the integration of existing individualized prediction tools into routine clinical decision making. The calculators predicted significantly worse than observed survival among patients who received induction chemotherapy and primary surgery, suggesting a need for updated consideration of modern treatment modalities. Further development of individualized prognostic calculators may improve risk prediction, treatment planning, and counseling for patients with laryngeal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…27, 46 In the current study, we found OPSCC calculators to yield higher AUCs and C-indices than did oral cavity and larynx models. This is likely due to the availability and incorporation of HPV, a robust biomarker in the OPSCC calculators.…”
Section: Discussionsupporting
confidence: 48%
“…27, 46 In the current study, we found OPSCC calculators to yield higher AUCs and C-indices than did oral cavity and larynx models. This is likely due to the availability and incorporation of HPV, a robust biomarker in the OPSCC calculators.…”
Section: Discussionsupporting
confidence: 48%
“…Though the TNM stage works well on the population level, it less effectively prognosticates at an individual level. Several nomograms, visual description of predictive statistical models for personalized patients, have been built to predict the survival probability in patients with laryngocarcinoma [9][10][11][12][13]. But these studies enrolled different patient cohorts (e.g., laryngeal cancer, advanced laryngeal cancer, and distant metastatic laryngeal carcinoma), and treatment modalities (i.e., radiotherapy vs. surgery).…”
Section: Introductionmentioning
confidence: 99%
“…Though the TNM stage works well on the population level, it less effectively prognosticates at an individual level. Several nomograms, are visual description of predictive statistical models for personalized patients, have been built to predict the survival probability in patients with laryngocarcinoma [9][10][11][12][13]. But these studies enrolled different patient cohorts (eg, laryngeal cancer, advanced laryngeal cancer, and distant metastatic laryngeal carcinoma), and treatment modalities (ie, radiotherapy vs surgery).…”
Section: Introductionmentioning
confidence: 99%
“…But these studies enrolled different patient cohorts (eg, laryngeal cancer, advanced laryngeal cancer, and distant metastatic laryngeal carcinoma), and treatment modalities (ie, radiotherapy vs surgery). Moreover, all these prediction models were created based on the population of western countries [9][10][11][12][13]. Due to difference in environmental exposures, ethnical diversity [14], adjuvant treatment after operation and treatment modalities, the clinical features of LSCC in eastern countries are also different from western countries.…”
Section: Introductionmentioning
confidence: 99%